280 The Use of Telemedicine in Plastics Surgery During COVID-19: A Single-Centre Correlation Study with Patient Reported Outcome Measures. (12th October 2021) - Rojoa, D; Raheman, F; Ibrahim, A; Patel, N
Abstract: Aim: With enforcement of social distancing measures during the COVID-19 pandemic, face-to-face patient contact was shifted to telemedicine consultations. There is limited evidence evaluating patient experience of follow-ups and expectations into quality metrics. Our aim was to perform a service evaluation by prospectively evaluating the management and outcomes of plastic surgery patients. Method: Patients were consecutively assessed over the COVID-19 lockdown period, from March to May 2020. They ranged from urgent cancer cases to burns and trauma. We used a questionnaire to evaluate initial treatment, wound care, complications, and overall service. A validated health-related quality of life (HRQL) survey was used to assess the impact of injury or wound on lifestyle and we also assessed patient enablement. Correlation analysis determined relationships between outcomes, service evaluations and HRQL variables. Results: 77 patients were consecutively treated in our unit, of which 46 completed the questionnaire. 42.2% used multimedia as mode of follow-up, including smart phones for messages and videocalls, and trust e-mails. There was a 3-fold increase in number of infections for non-face-to-face consultations, with a correlation significance of 0.043. We found no correlation between age and wound complication rates. 72.7% of patients found overall service very good or excellent. Although overall service satisfaction was similar for multimedia use and face-to-face consultations (p = 0.02), less patients were confident looking after their wound without face-to-face follow-ups. Conclusions: COVID-19 has brought upon an unprecedented change in practice in our department. Implementing multimedia use and educating patients on wound care can significantly improve efficiency and service provision.